Research Status and Current Problems of Corpus Linguistics in China - Yue, Liao; Kunyu, Li (Sinología hispánica. China Studies Review, 2024)
After more than 40 years of development, China has made significant achievements in corpus-based research, while problems still remain: corpus-based studies of linguistic phenomena are not thorough enough, practice and research have not yet been bridged, and while the English corpus has made significant progress, the multilingual one lag far behind. It has become urgent to accelerate the construction of corpora in China to keep pace with international corpora. With the development of linguistics research on Chinese corpus and corpus construction in China as the research object, this study has adopted both diachronic and synchronic research methods, combing the history and current studies in corpus linguistics in China systematically. The paper is designed to summarize the current bottlenecks and problems of Chinese corpus construction with academic consensus, and to comprehensively and objectively analyze the problems in Chinese corpus linguistics research and the difficulties in solving these problems. Hopefully, it could draw the attention of academic circles in China and abroad, provide international experience in advanced corpus construction, solve the problems restricting the development of Chinese corpus, and promote corpus linguistics research and corpus construction in China.